Vitamin C and vitamin D3 alleviate metabolic-associated fatty liver disease by regulating the gut microbiota and bile acid metabolism via the gut-liver axis - Chen, Qingling; Zhao, Lili; Mei, Ling; Zhao, Xiaotong; Han, Ping; Liu, Jie; Meng, Chao; Li, Ruifang; Zhong, Rui; Wang, Kai; Li, Jia (Frontiers in Pharmacology, 2023)
Background: Previous studies have demonstrated that both vitamin C (VC) and vitamin D3 (VD3) have therapeutic potential against metabolic disorders, including obesity, diabetes, and metabolic-associated fatty liver disease (MAFLD). However, it is unclear whether VC supplementation is associated with improving the intestinal flora and regulating the metabolism of bile acids via the gut-liver axis in MAFLD. There is still no direct comparison or combination study of these two vitamins on these effects. Methods: In this study, we employed biochemical, histological, 16S rDNA-based microbiological, nontargeted liver metabolomic, and quantitative real-time polymerase chain reaction analyses to explore the intervening effect and mechanism of VC and VD3 on MAFLD by using a high-fat diet (HFD)-induced obese mouse model. Results: Treatment of mice with VC and VD3 efficiently reversed the characteristics of MAFLD, such as obesity, dyslipidemia, insulin resistance, hepatic steatosis, and inflammation. VC and VD3 showed similar beneficial effects as mentioned above in HFD-induced obese mice. Interestingly, VC and VD3 reshaped the gut microbiota composition; improved gut barrier integrity; ameliorated oxidative stress and inflammation in the gut-liver axis; inhibited bile acid salt reflux-related ASBT; activated bile acid synthesis-related CYP7A1, bile acid receptor FXR, and bile acid transportation-related BSEP in the gut-liver axis; and improved bile secretion, thus decreasing the expression of FAS in the liver and efficiently ameliorating MAFLD in mice. Conclusion: Together, the results indicate that the anti-MAFLD activities of VC and VD3 are linked to improved gut-liver interactions via regulation of the gut microbiota and bile acid metabolism, and they may therefore prove useful in treating MAFLD clinically.